Investigation of Mechanisms in Bone Conduction Hyperacusis With Third Window Pathologies Based on Model Predictions - Stenfelt, Stefan (Frontiers in Neurology, 2020)
A lumped element impedance model of the inner ear with sources based on wave propagation in the skull bone was used to investigate the mechanisms of hearing sensitivity changes with semi-circular canal dehiscence (SSCD) and alterations of the size of the vestibular aqueduct. The model was able to replicate clinical and experimental findings reported in the literature. For air conduction, the reduction in cochlear impedance due to a SSCD reduces the intra-cochlear pressure at low frequencies resulting in a reduced hearing sensation. For bone conduction, the reduced impedance in the vestibular side due to the SSCD facilitates volume velocity caused by inner ear fluid inertia, and this effect dominates BC hearing with a third window opening on the vestibular side. The SSCD effect is generally greater for BC than for AC. Moreover, the effect increases with increased area of the dehiscence, but areas more than the cross section area of the semi-circular canal itself leads to small alterations. The model-predicted air-bone gap for a SSCD of 1mm2 is 30 dB at 100 Hz that decreases with frequency and become non-existent at frequencies above 1 kHz. According to the model, this air-bone gap is similar to the air-bone gap of an early stage otosclerosis. The normal variation of the size of the vestibular aqueduct do not affect air conduction hearing, but can vary bone conduction sensitivity by up to 15 dB at low frequencies. Reinforcement of the OW to mitigate hyperacusis with SSCD is inefficient while a RW reinforcement can reset the bone conduction sensitivity to near normal.